An Introduction to Computer Graphics for Artists - Paquette, Andrew; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
An Introduction to Computer Graphics for Artists is an application-independent, reader-friendly primer for anyone with a serious desire to understand 3D Computer Graphics. Written by a veteran of the computer graphics industry whose previous career included film animation and various spells as Art Director for video games, Andrew Paquette draws on his experiences both as an artist and a manager. Far too often artists, even professionals, lack a basic understanding of the principles of computer graphics. The result is inefficiency and lower quality of work. This book addresses these issues by providing fundamental information in a university course format, with theoretical material, detailed illustrations, and projects to test the reader$1 (Bs understanding of the concepts covered. Opening with the first and most basic elements of computer graphics, the book rapidly advances into progressively more complex concepts. Each of the elements, however simple, are important to understand because each is an essential link in a chain that allows an artist to master any computer graphics application. With this accomplished, the artist can use technology to satisfy his goals, instead of the technology being master of the artist. All students wanting to learn more about computer graphics from an artistic viewpoint, particularly those intending to pursue a career in computer game design or film animation, will find this book invaluable.s
Preface -- Acknowledgements -- List of Figures -- List of Tables -- Introduction -- CG Basics -- Observation Skills -- Measurements -- Modeling 1: Polygons -- Resolution -- Optimization -- Validation -- Texture Coordinates (UVs) -- Shaders and Texturing -- Rendering -- Animation -- Modeling 2: NURBS -- Modeling 3: Advanced -- Industry Standards -- Appendix -- Glossary -- Index.
Keywords: Computer science; Computer vision; Computer graphics; Information systems; Arts; Computer Science; Computer Graphics; Arts; Computer Imaging, Vision, Pattern Recognition and Graphics; Computer Appl. in Arts and Humanities